The Mediating-Moderating Role in The Relationship Between Self-Efficacy and Academic Boredom: A Meta-Analytic Approach - Ghozali Rusyid Affandi; Cholichul Hadi; Nur Ainy Fardana; Mohd Nazri Bin Abdul Rahman; Xinyue Yang (Yayasan Keluarga Guru Mandiri, 2025)
Academic boredom can adversely affect student motivation and performance, necessitating an exploration of its psychological foundations. This meta-analysis delves into the interplay between self-efficacy and academic boredom, underscoring the significance of mediators and moderators in this dynamic. A systematic review across various databases, including ScienceDirect, Web of Science, SCOPUS, ProQuest, Emerald Insight, and Springer Link, identified 17 relevant studies, encompassing 8631 participants. The quality of these studies was scrutinized using the JBI Critical Appraisal Checklist. The meta-analysis, which utilized a random-effects model, found a noteworthy negative correlation between self-efficacy and academic boredom (r = -0.34, p 0.05). The analysis revealed high heterogeneity (I² = 91.49%), indicating significant differences among the studies. Additional findings pointed to social interaction and task performance as essential mediators, while factors such as the learning environment and genetics, notably MAOA, served as moderators. This research suggests that self-efficacy can act as a buffer against academic boredom, highlighting the importance of interventions that enhance self-efficacy and promote engaging learning environments. This study contributes to formulating effective strategies to combat academic boredom and improve student educational outcomes by integrating cognitive, emotional, and contextual factors.